ANALISIS DAN REDESAIN RPS BERBASIS RISET UNTUK MENINGKATKAN KEMAMPUAN 6C MAHASISWA PADA MATA KULIAH BAHASA INDONESIA - Welsi Damayanti; Ahmad Fuadin; Rama Wijaya Abdul Rozak (Jurnal Semantik, 2023)
This research aims to update the Semester Learning Plan (RPS) which prioritizes research to improve the 6C (Communication, Collaboration, Critical Thinking, Creativity, Compassion, and Computational Thinking) skills of students in the Indonesian Language Course. This research adopts a qualitative approach with a descriptive method. Data was collected through a review of existing RPS and interviews with Indonesian language lecturers. The results of the study of RPS indicated that the development of 6C skills in students had not been optimal in the existing RPS. Improvement of RPS includes learning strategies that encourage communication, collaboration, creative expression of ideas, and the application of computational thinking in the use of technology. The updated RPS is implemented in teaching Indonesian. Positive responses were received from students who were involved, showing a good response to a more active and collaborative learning approach. The results of this study confirm that improving RPS based on research is effective in improving students' 6C skills in the context of Indonesian Language Courses. The implications of this research emphasize the importance of developing RPS that supports the mastery of 6C skills in order to prepare students to face the increasingly complex and dynamic requirements of the world of work.